Retracted: Bone Mineral Density Predicts Fractures in Chronic Kidney Disease. (16th April 2015) - West, Sarah L.; Lok, Charmaine E.; Langsetmo, Lisa; Cheung, Angela M.; Szabo, Eva; Pearce, Dawn; Fusaro, Maria; Wald, Ron; Weinstein, Jordan; Jamal, Sophie A.
ABSTRACT: Fractures are common in chronic kidney disease (CKD). The optimal methods by which to assess fracture risk are unknown, in part, due to a lack of prospective studies. We determined if bone mineral density (BMD) by dual‐energy X‐ray absorptiometry (DXA), and/or high‐resolution peripheral quantitative computed tomography (HRpQCT) could predict fractures in men and women ≥18 years old with stages 3 to 5 CKD. BMD was measured by DXA (at the total hip, lumbar spine, ultradistal, and 1/3 radius) and by HRpQCT (at the radius), and subjects were followed for 2 years for incident morphometric spine fractures and low‐trauma clinical fractures. The mean age of the subjects was 62 years with equal numbers having stages 3, 4, and 5 CKD. Over 2 years there were 51 fractures in 35 subjects. BMD by DXA at baseline was significantly lower at all sites among those with incident fractures versus those without. For example, the mean BMD at the total hip in those with incident fractures was 0.77 g/cm 2 (95% confidence interval [CI], 0.73 to 0.80) and in those without fracture was 0.95 g/cm 2 (95% CI, 0.92 to 0.98). Almost all baseline HRpQCT measures were lower in those with incident fracture versus those without. For example, volumetric BMD in those with incident fractures was 232 mg HA/cm 3 (95% CI, 213 to 251) and in those without fracture was 317.6 mg HA/cm 3 (95% CI, 306 to 329.1). Bone loss occurred in all subjects, but was significantly greater among those with incident fractures. Our data demonstrate that low BMD (by DXA and HRpQCT) and a greater annualized percent decrease in BMD are risk factors for subsequent fracture in men and women with predialysis CKD. © 2014 American Society for Bone and Mineral Research.